2022
DOI: 10.3389/fimmu.2022.953043
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of positive antiphospholipid antibodies in pregnant women with SARS-CoV-2 infection and impact on pregnancy outcome: A single-center prospective study on 151 pregnancies

Abstract: Background: At the beginning of the SARS-CoV-2 pandemic, there was a lack of information about the infection's impact on pregnancy and capability to induce de novo autoantibodies. It soon became clear that thrombosis was a manifestation of COVID-19, therefore the possible contribution of de novo antiphospholipid antibodies (aPL) raised research interest. We aimed at screening SARS-CoV-2 positive pregnant patients for aPL. Methods:The study included consecutive pregnant women who were hospitalized in our Obstet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In three LAC positive patients with 12-week follow-up testing, Gozzoli et al found all were LAC negative. 48 We identified LAC positivity persisted in one of two patients with follow-up data. It is unknown if persistent LAC positivity in this population has clinical implications for subsequent pregnancies or thrombotic risk.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In three LAC positive patients with 12-week follow-up testing, Gozzoli et al found all were LAC negative. 48 We identified LAC positivity persisted in one of two patients with follow-up data. It is unknown if persistent LAC positivity in this population has clinical implications for subsequent pregnancies or thrombotic risk.…”
Section: Discussionmentioning
confidence: 65%
“…In a single-center, prospective cohort study of 151 individuals admitted to Labor and Delivery with SARS-CoV-2 infection (symptomatic or asymptomatic) tested for antiphospholipid antibodies (LAC, anti-β2 glycoprotein I, and anticardiolipin), Gozzoli et al found that 16 patients had at least one positive antibody of which 9 individuals (6.0%) were LAC positive. 48 Those with a positive antiphospholipid antibody had a higher rate of preeclampsia compared with those without a positive antiphospholipid antibody (25 vs. 5%; p ¼ 0.004). There was a single thrombosis identified in an antiphospholipid antibody negative patient.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation